Developing BRICS+ Digital Technologies: the Russian contribution in the field of scientific and educational diplomacy - Kotova, Yulia (InterAção, 2025)
According to the United Nations Conference on Trade and Development, the world is going through a ‘fifth technological revolution’. Digitalization, artificial intelligence, cognitive research, neurotechnology and cryptocurrencies have radically changed the very nature of international relations and world politics. In these conditions, the countries of the World Majority are faced with the questions of how to ensure economic and technological sovereignty and formulate a development policy in the context of global high-tech inequality. This issue is particularly clearly visible in the agenda of BRICS+, a global association whose values, include inclusiveness and advancement based on scientific achievements, equality, progress and sustainable development. The Russian Federation, as one of the member countries of the association, is among the international actors advocating for technological sovereignty and its protection, as well as equal access to modern technologies. BRICS+ has the potential to become a leading platform for sharing innovations, especially in science and education. Russia is capable of making a significant contribution in these areas since it is known worldwide for its fundamental science, traditions of preparing highly qualified personnel and educational system. Moreover, in recent years the country has acquired unique experience and its own domestic producers interested in distributing their products and services. Russia is able to offer BRICS+ members a transfer of a number of high-tech and promising initiatives in the field of science and education, which are designed to strengthen the positions of states in the international arena and prepare them for all sorts of risks and threats.